Unique radio innovation for the 21st century building scalable and global RFID networks - Ranasinghe, Damith C.; Sheng, Quan Z.; Zeadally, Sherali (Springer, 2010)
Are you an engineer or a researcher developing RFID systems? Are you a manager considering deploying RFID-based applications? If so, this book is for you. Covering modern RFID systems, the challenges to RFID implementation are addressed using specific industrial research examples and common integration issues. The primary focus is on answering questions surrounding building scalable global Internet-based RFID networks. Key topics include RFID data management, RFID data processing and integration, Real-Time Locating Systems (RTLS) and sensors. The book considers the challenges of and solutions to building and exploiting global networks to guarantee one of the most important business drivers for modern RFID technology: traceability. The authors have drawn together RFID applications from the retail supply chain, asset and product lifecycle management, anti-counterfeiting and cold chain management to explore how global traceability networks can be created using RFID and sensor technologies. They present insights from world's leading research laboratories.